2017
DOI: 10.1007/s11128-017-1786-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving the capacity of quantum dense coding by weak measurement and reversal measurement

Abstract: A protocol of quantum dense coding protection of two qubits is proposed in amplitude damping (AD) channel using weak measurement and reversal measurement. It is found that the capacity of quantum dense coding under the weak measurement and reversal measurement is always greater than that without weak measurement and reversal measurement. When the protocol is applied, for the AD channels with different damping coefficient, the result reflects that quantum entanglement can be protected and quantum dense coding b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the literature, several studies have both theoretically proposed and experimentally demonstrated the concept of dense coding (see, e.g., [9][10][11][12][13][14][15][16][17] and references quoted therein). Interestingly, different methods have been presented to protect the quantum advantages of dense coding under decoherence for a relatively long time [18][19][20][21][22][23], such as choosing the proper initial channel state [24,25], employing different configurations for the external noise [26,27], and applying the quantum weak measurement (QWM) operation [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several studies have both theoretically proposed and experimentally demonstrated the concept of dense coding (see, e.g., [9][10][11][12][13][14][15][16][17] and references quoted therein). Interestingly, different methods have been presented to protect the quantum advantages of dense coding under decoherence for a relatively long time [18][19][20][21][22][23], such as choosing the proper initial channel state [24,25], employing different configurations for the external noise [26,27], and applying the quantum weak measurement (QWM) operation [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tian and Zhang [36] proposed a scheme to improve the capacity of super dense coding by using weak measurement (WM) and quantum measurement reversal (QMR) in the AD channel. The basic idea can be expressed as: WM −→ AD channel −→ QMR −→ super dense coding.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that their quantum advantages may exist for a relatively long time by choosing specific channel states [ 24 , 25 ], by using the desired features (the non-Markovianity, the correlated actions, etc.) of the noises [ 26 , 27 , 28 ], or by applying active operations, such as local filtering operations [ 27 ] and weak measurements [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%